2021
DOI: 10.1021/acschemneuro.1c00376
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Histidine Tautomerism Effect on the Initial Stages of Prion Misfolding: New Insights from a Computational Perspective

Abstract: The aggregation and structural conversion of normal prion peptide (PrP C ) into the pathogenic scrapie form (PrP Sc ), which can act as a seed to enhance prion amyloid fiber formation, is believed to be a crucial event in prionopathies. Previous research suggests that the prion monomer may play an important role in oligomer generation during disease pathogenesis. In the present study, extensive replica-exchange molecular dynamics (REMD) simulations were conducted to explore the conformational characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…38,39,[51][52][53][54][55][56] Histidine behavior in illnesses with misfolded proteins has been a significant problem in numerous research studies. [57][58][59][60] Owing to net charge shifts and varying N/N-H position on imidazole rings, histidine behaviors (containing tautomeric behaviors and protonation behaviors) are hypothesized to be a root cause of protein folding and/or misfolding 57,[60][61][62][63][64] (Scheme 1). In the imidazole ring, there are two intrinsically changeable isomeric forms (N-e (HIE, e) and N-d (HID, d) states) and a protonated form (both e and d states, described as p state) that play an active role in Ab misfolding.…”
Section: Introductionmentioning
confidence: 99%
“…38,39,[51][52][53][54][55][56] Histidine behavior in illnesses with misfolded proteins has been a significant problem in numerous research studies. [57][58][59][60] Owing to net charge shifts and varying N/N-H position on imidazole rings, histidine behaviors (containing tautomeric behaviors and protonation behaviors) are hypothesized to be a root cause of protein folding and/or misfolding 57,[60][61][62][63][64] (Scheme 1). In the imidazole ring, there are two intrinsically changeable isomeric forms (N-e (HIE, e) and N-d (HID, d) states) and a protonated form (both e and d states, described as p state) that play an active role in Ab misfolding.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth understanding of tautomers is of great significance for the study of organic reaction mechanisms, base pairing and replication, and optical rotation of sugars. [1][2][3] Different from being in dynamic equilibrium in the gas and liquid phases, tautomers exist in a relatively stable form in the solid phase. 4 Solid-state separation provides an opportunity to study the physical and chemical properties of different tautomers.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, a novel histidine tautomerism/protonation hypothesis accounting for the pathogenesis of AD and other neurological diseases has been suggested by our research team. 11–26 We have demonstrated that different protonated states in the histidine imidazole ring are related to the conformational characteristics of diverse misfolded peptides (namely Aβ, tau, amylin, and prion) and can influence fibrillization processes in polypeptides, resulting in proteopathies. This histidine hypothesis implies that protein accumulation may occur inherently rather than as a consequence of extrinsic agents.…”
Section: Introductionmentioning
confidence: 99%